(untitled) (Academia Journal of Medicine, 2021)
Background: To study the association of Non Alcoholic Fatty Liver Disease in patients of Coronary Artery Disease. Subjects and Methods: 100 patients of established CAD admitted were included in the study. Patients were screened for NAFLD with USG. 2 groups were made: CAD with NAFLD & CAD without NAFLD and comorbidities were identified and evaluated for Risk Factors and Correlation was identified. Result: Majority of study subjects (79%) were males and 21% were females. Highest proportion of subjects (29%) were in 51-60 years of age and lowest (9%) in above 70 years of age. Chest pain was the commonest presenting symptom preceding breathlessness and sweating. In the fatty liver group, a high proportion of subjects had history of Type-II DM (31% vs 4%) and Hypertension (18% vs 11%) in comparison to normal liver group. The mean BMI of study participants in the present study was 29.5 kg/m2. In fatty liver group, higher proportion of subjects had fasting blood glucose levels > 126 (66.7%) than the non-fatty liver subjects (3.8%). higher proportion of subjects had total cholesterol levels higher than 200 (14.6%) than the non-fatty liver subjects (1.9%). In group with non-fatty liver, greater proportion of subjects had LDL levels higher than 100 (40.4%) than the fatty liver group (33.3%). it was found that 37.5% subjects had mild grade of NAFLD whereas 43.8% had moderate grade and 18.7% had severe grade of NAFLD. Conclusion: There is a significant relationship between NAFLD and an elevated CVD risk in those with or without Metabolic Syndrome.